Tinjauan Kriminologis terhadap Pelaku Tawuran antar Remaja di Wilayah Hukum Polresta Serang Kota - Putri, Septia Nanda; Hibar, Ujang; Jumhana, Enjum (Universitas Batanghari Jambi, 2025)
The purpose of this research is to examine a criminological perspective on the perpetrators of youth brawls and to review the role of the police in addressing these incidents. This study uses a normative-empirical legal research approach, employing an empirical case study on social behavior, focusing on actual behavior as a social phenomenon, supplemented by secondary data in the form of positive legal rules and documents. Based on the findings, it can be concluded that criminology, as a science related to the involvement of individuals in delinquent behavior as a social phenomenon, views brawls as a violation of the law. Several factors contribute to why teenagers engage in criminal behavior as a form of juvenile delinquency, such as a lack of parental communication and affection, weak self-control in adolescents, and environmental factors, all of which are interconnected and can lead to juvenile delinquency. There is no specific reason for why they participate in these brawls. In terms of punishment, the police take many factors into consideration when dealing with minors involved in the legal system, and it is not uncommon for these teenagers to be returned to their parents. However, there are exceptions if the incident results in serious injury or death, in which case further legal action is taken. The efforts made by the Serang City Police Department to tackle youth brawls and delinquency include pre-emptive and preventive measures.